1993
DOI: 10.1002/eji.1830230432
|View full text |Cite
|
Sign up to set email alerts
|

A subset of anti‐CD21 antibodies promote the rescue of germinal center B cells from apoptosis

Abstract: Germinal center cells (GCC) are programmed to die by apoptosis unless they receive a positive signal for rescue. The primary signal in vivo is believed to be dependent on interaction with antigen held as immune complexes on follicular dendritic cells (FDC), a subset of which express large amounts of CD23, a low-affinity receptor for IgE. Recombinant soluble CD23 (sCD23) and interleukin-1 have been found to potentiate the survival of GCC in vitro. Recently, CD23 was shown to interact specifically with a ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…Of greatest relevance to the present work, Bonnefoy et al (69) reported that in vitro engagement of CD21 on human germinal center B cells promoted cell viability via a Bcl-2-dependent mechanism (70). Additionally, Roberts and Snow (23) noted that engagement of CD19 on LPSactivated murine B cells promoted both increased Bcl-2 expression and increased proliferation.…”
Section: Discussionmentioning
confidence: 58%
“…Of greatest relevance to the present work, Bonnefoy et al (69) reported that in vitro engagement of CD21 on human germinal center B cells promoted cell viability via a Bcl-2-dependent mechanism (70). Additionally, Roberts and Snow (23) noted that engagement of CD19 on LPSactivated murine B cells promoted both increased Bcl-2 expression and increased proliferation.…”
Section: Discussionmentioning
confidence: 58%
“…CD23 is an immunoregulatory protein found both on cell membranes and as a soluble protein. CD23 interacts with CR2 to increase production of IgE in the presence of IL-4 (3), rescue germinal-center B cells from apoptosis (24), provide T cell-activating signals by B cell APCs (25), and promote T-B cell adhesion (26).…”
Section: H Uman Complement Receptor (Cr)mentioning
confidence: 99%
“…Interaction of CD21 with CD23 on B-cells is believed to additionally protect B-cells from apoptosis (Bonnefoy et al, 1993). However, the function of CD21 on most other cell types remains unknown.…”
Section: Introductionmentioning
confidence: 99%